Bilateral sudden sensorineural hearing loss in a patient with scrub typhus: a case report - Babu, Mosin; Singh, Thingbaijam Sudhiranjan; Yumlembam, Shandhyalata; Juhy, Nimitha A. M.; Meetei, Shapam Ravi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Scrub typhus is a febrile illness caused by Orientia tsutsugamushi, a gram negative alpha proteobacterium and transmitted by the bite of leptotrombidium, chigger mite larvae. The disease is endemic to Southeast Asia and Northern Australia and derives its name from the vegetation that harbours the mite. The patient usually presents with high-grade fever, an eschar at the inoculation site, generalised lymphadenopathy, organomegaly and pneumonitis. Rarely, the patient may go into acute renal failure, disseminated intravascular coagulation and shock. A case of scrub typhus presenting with acute sensorineural hearing loss which resolved with treatment is being reported. Hearing impairment with fever in a patient in endemic region of scrub typhus can give a clue to health care worker towards the diagnosis of scrub typhus and thus early administration of treatment.